"Shame on you": The impact of shame in body-focused repetitive behaviors and binge eating. (March 2021) - Houazene, S.; Leclerc, J.B.; O'Connor, K.; Aardema, F.
Abstract: Body-focused repetitive behaviors (BFRBs), such as hair-pulling, skin-picking, and nail-biting, have been associated with difficulties in emotion regulation. Studies have suggested that aversive emotions are important triggers for impulsive behaviors such as BFRBs and binge eating. In particular, shame has been hypothesized to be a key emotion before and after these behaviors, but no experimental studies yet have investigated its impact on BFRBs. We aimed to evaluate the role of shame in BFRB and binge eating episodes and the presence of shame following these behaviors. Eighteen women with BFRBs, 18 with binge eating, and 18 community controls participated in the study. Results showed that an experimental shame condition triggered more shame in the binge eating and BFRB groups than in the control group. In addition, the shame induced condition increased the urge to engage in BFRBs, but not in binge eating. Results showed that participants from the BFRB and the binge eating groups reported more shame after engaging in their pathological behaviors compared to following the neutral condition. Future studies should replicate these findings with larger samples and different shame-inducing conditions. Highlights: Shame increases the urge to engage in BFRBs, but not the urge to engage in binge eating. People suffering from BFRBs and binge eating report feeling shameful retrospectively after engaging in BFRB or binge eating episodes. Findings support the presence of a cycle of shame in BFRBs. The BFRB and binge eating groups experienced a higher sensitivity to shame following a shame-inducing task than controls.